Teachers’ Perspectives on AI-Based Learning for Vocabulary Retention: Evidence from Indonesian Primary Schools - Muhammad Helmi Nur Mufid Subagyo; Nur Hidayat; Dewi Candraningrum (Universitas Al-Qolam Malang, 2026)
This study explores the extent to which artificial intelligence (AI)-based technology contributes to vocabulary retention and student engagement in English language learning at the primary school level in Indonesia. Employing a qualitative descriptive approach, data were gathered from seven primary school English teachers through open-ended questionnaires. Thematic analysis was used to identify key patterns in their responses. Findings indicate that AI-based learning tools, such as gamified applications and educational chatbots, play a pivotal role in enhancing students’ vocabulary memorization by offering visual stimuli, instant feedback, and personalized learning experiences. Additionally, the integration of AI fosters greater student participation and motivation by making learning more interactive and engaging. Despite these benefits, several challenges were reported, including limited access to digital infrastructure, unstable internet connectivity, and insufficient teacher training in technology integration. Teachers also expressed concerns about the potential decline in students’ social interaction due to overreliance on AI. Nevertheless, respondents conveyed optimism regarding AI's long-term potential to support adaptive and differentiated learning for young learners. This study contributes to the growing body of knowledge on educational technology by presenting empirical evidence from primary classrooms. It also offers recommendations for stakeholders to address infrastructure and training gaps to ensure equitable and effective AI integration in language education. The implications are especially relevant as digital transformation policies in education gain momentum globally.